Effectiveness of Stakeholder Collaboration in Jakarta FIR Governance for Airspace Security - Arie Prihandoko Dalirianto; Hidayat Hidayat; Encep Sopandi (CV. Austronesia Akademika, 2025)
Indonesia’s airspace security represents a strategic dimension of national sovereignty, given its position as the world’s largest archipelagic state with vast airspace intersected by dense international flight routes. The transfer of the Jakarta Flight Information Region (FIR) from Singapore to Indonesia created opportunities for strengthening sovereignty while also posing significant challenges in coordination, regulation, and technological readiness. This study aims to analyze the existing conditions of stakeholders, evaluate the effectiveness of their roles, and propose an ideal governance model for safeguarding Indonesia’s airspace. Employing a descriptive qualitative method with a case study approach, the research collected data through literature review, in-depth interviews, and documentation from relevant institutions, analyzed inductively with source and theory triangulation to ensure validity. The findings indicate persistent issues such as overlapping authority, limited radar technology, and weak inter-agency communication, which reduce the responsiveness of cross-agency coordination to airspace violations. Nonetheless, positive developments are observed through the establishment of inter-agency coordination forums and central government commitment to sovereignty reinforcement. The study concludes that an effective governance model requires multi-level collaboration that integrates military, civil, and international diplomatic dimensions supported by modern technology and robust regulation. Recommendations include enhancing inter-agency coordination, developing an integrated radar system, improving human resources through international-standard training, and institutionalizing a sustainable governance framework responsive to global aviation dynamics. This research contributes both academically and practically to public policy formulation in managing Indonesia’s national airspace.